2017
DOI: 10.1186/s10397-017-1031-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomized control trial to evaluate the importance of pre-training basic laparoscopic psychomotor skills upon the learning curve of laparoscopic intra-corporeal knot tying

Abstract: BackgroundTraining of basic laparoscopic psychomotor skills improves the acquisition of more advanced laparoscopic tasks, such as laparoscopic intra-corporeal knot tying (LICK). This randomized controlled trial was designed to evaluate whether pre-training of basic skills, as laparoscopic camera navigation (LCN), hand-eye coordination (HEC), and bimanual coordination (BMC), and the combination of the three of them, has any beneficial effect upon the learning curve of LICK. The study was carried out in a privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Carlos et al [ 14 ] showed that pre-training in hand–eye coordination with both the dominant and non-dominant hands shortens the learning curve. When the 8K UHD image quality was utilized with both hands, decent hand–eye coordination was achieved, and “pseudo 3D imaging” was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Carlos et al [ 14 ] showed that pre-training in hand–eye coordination with both the dominant and non-dominant hands shortens the learning curve. When the 8K UHD image quality was utilized with both hands, decent hand–eye coordination was achieved, and “pseudo 3D imaging” was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing with single-hand manipulation, double-hand manipulation of the instruments was relatively easier for the operator to establish the laparoscopic depth perception [ 13 ]. In order to separate the peritoneum from the vas deferens conveniently, an assistant dissecting forceps was necessary for laparoscopic extraperitoneal closure of the internal ring.…”
Section: Discussionmentioning
confidence: 99%
“…For the novices, they not only faced with depth perception difficulty, but also eye-hand coordination difficulty. And double-hand manipulation was beneficial for depth perception and orientation perception, which were the cornerstones for laparoscopic surgery [ 13 , 14 ]. Umbilical one site two-port laparoscopic method achieved the same cosmetic effect with that of the single-port laparoscopic one [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In open surgery, for example, the most critical attributes that a surgeon should possess are hand–eye coordination and finger dexterity. [ 9 ] In medical ultrasound imaging, psychomotor skills (visuomotor and visuospatial) are central. [ 10 ] Core abilities (e.g., psychomotor skills, visuospatial ability, and depth perception) are vital for catheter-based interventions, natural orifice transluminal endoscopic surgery, robotic surgery, and other procedural interventions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Laparoscopic surgery requires both surgical and psychomotor skills (e.g., camera navigation, hands–eyes coordination, and bimanual coordination). [ 9 11 ]…”
Section: Introductionmentioning
confidence: 99%